ANALISIS TINGKAT KEPATUHAN MAHASISWA DALAM PENERAPARAN SOP K3 DI LABORATORIUM JURUSAN TEKNOLOGI LABORATORIUM MEDIK POLTEKKES PALEMBANG - Zulfahmi Eko Saputra; Arie Tri Wahyudi; Dianita Ekawati (Journal of Innovation Research and Knowledge, 2025)
Occupational Health and Safety (OHS) is a critical aspect of laboratory activities, particularly in microbiology and hematology laboratories with high-risk environments. This study aimed to assess student compliance levels and analyze the influencing factors in implementing Standard Operating Procedures (SOPs) for OHS in the Laboratory of the Medical Laboratory Technology Department at Poltekkes Kemenkes Palembang. A quantitative cross-sectional approach was used with 60 student respondents. Data were analyzed using chi-square tests and multiple logistic regression. Results showed a generally high level of compliance, with 73.3% of students classified as compliant. However, 26.7% were non-compliant, indicating the need for continuous improvement efforts. Of the eight variables tested, only the use of personal protective equipment (PPE) showed a statistically significant relationship with compliance (p < 0.001; OR = 147), making it the strongest predictor in the multivariate model. In contrast, variables such as gender, knowledge, handling of chemical/infectious materials, use of heating equipment, accident response, supervision, and laboratory facilities showed no significant relationship. These findings suggest that student compliance is not solely influenced by individual or cognitive factors but also by systemic, environmental, and collective safety culture aspects. Strengthening institutional policies, regular supervision, and consistent safety education are essential to foster a sustainable culture of compliance